(untitled) (Proceedings of the International Conference on Agriculture, 2023)
Sustenance of local farming systems (FS) is inevitably linked with resource-endowment and the attributes of communities associated with them, playing a key role in ensuring rural food security. Hypothesizing that the local communities adopt collective action under resource-scarce contexts in community-managed FSs, this study explores the drivers and role of collective action in sustainable management of rural FSs. The study context refers to resource scarcity induced by impacts of climate change and severe economic crisis on the FSs established under Village-Tank-Cascade-Systems(VTCS) in the rural dry zone of Sri Lanka. Medde-Rambewa cascade system located in Nawagattegama, Puttalam district of Sri Lanka was the geographical scope of the study. Case-study approach was used with mixed methods of data collection and analysis. A household questionnaire survey (n=88), focused group discussions, in-depth interviews and field observations were used for primary data collection. Based on the findings, community members were found to adopt collective strategies for scarce resource management when they perceive themselves as key stakeholders in the sustenance of resource systems, coupled with awareness on causes (X2(1, N=88) =4.29, p=0.038) and effects (X2(1, N=88) =6.41, p=0.011) of resource degradation in the FSs established under VTCS. Collective irrigation-water sharing (Bethma) in lowland FSs (92%), sharing of labour (34%) and other farming inputs (seeds, fertilizer and machinery) (64%) were found to be adopted as strategies in response to resource scarcity. Findings support the hypothesis and the study concludes that resource scarcity itself, community members’ recognition on their role as key stakeholders of resource management and awareness on the nature of resource endowment are drivers of collection action within communities managing FSs established under VTCS, ultimately contributing to ensure rural food security.